A danger to avoid or nothing to worry about? China and the protests in Korea during 2016–2017. Issue 1 (March 2023) - Cho, Sunghee
"Diffusion-proofing" literature discusses the measures taken by authoritarian regimes to prevent the diffusion of protests from other authoritarian states. What about protests in a neighboring democracy? Do they also fear diffusion due to the proximity, or are they not concerned because of the difference in regime type? This study analyzes Chinese state-run news outlets' portrayals of Korean protests calling for the president's impeachment from October 2016 to March 2017, based on the frequency and the focus of the reports as well as the descriptions of protests/protesters and the Korean government. The findings indicate that China did not fear the diffusion effect, as shown in their positive descriptions of the protests and protesters in frequent and detailed reports, although they adopted a cautious approach, with reports focusing more on the government side and emphasizing the public's frustration, low government support, and the president's wrongdoing. Overall, China appeared to be less concerned about the diffusion effect due to the regimes' dissimilarity.